Health effects of voluntary exposure to cold water - a continuing subject of debate - Espeland, Didrik; de Weerd, Louis; Mercer, James B. (International journal of circumpolar health, 2022)
This review is based on a multiple database survey on published literature to determine the effects on health following voluntary exposure to cold-water immersion (CWI) in humans. After a filtering process 104 studies were regarded relevant. Many studies demonstrated significant effects of CWI on various physiological and biochemical parameters. Although some studies were based on established winter swimmers, many were performed on subjects with no previous winter swimming experience or in subjects not involving cold-water swimming, for example, CWI as a post-exercise treatment. Clear conclusions from most studies were hampered by the fact that they were carried out in small groups, often of one gender and with differences in exposure temperature and salt composition of the water. CWI seems to reduce and/or transform body adipose tissue, as well as reduce insulin resistance and improve insulin sensitivity. This may have a protective effect against cardiovascular, obesity and other metabolic diseases and could have prophylactic health effects. Whether winter swimmers as a group are naturally healthier is unclear. Some of the studies indicate that voluntary exposure to cold water has some beneficial health effects. However, without further conclusive studies, the topic will continue to be a subject of debate.